Navigating Opportunities And Ethical Challenges In Facebook-Based Islamic Da’wah: A Critical Study Of Strategies In The Contemporary Era - M. Gufran; Rachmah Ida; Bagong Suyanto (INJECT (Interdisciplinary Journal of Communication), 2025)
This study explores the utilization of Facebook as a medium for Islamic da'wah in the contemporary era, highlighting its potential, advantages, and accompanying challenges. The method employed is a literature review with a narrative-descriptive approach. Data were collected from indexed and relevant scholarly articles and analyzed thematically to portray the dynamics of digital da'wah. The findings indicate that Facebook offers a broad, fast, and interactive space for da'wah through features such as live streaming, da'wah groups, and visual content. The platform’s strengths lie in its ability to reach younger generations, foster digital spiritual communities, and support contextual two-way communication. However, challenges also arise, such as the proliferation of hate speech, the spread of hoaxes, negative comments, and the emergence of unqualified preachers lacking sufficient knowledge and digital ethics. Additionally, the pressure to gain popularity often obscures the substance of da'wah. Therefore, effective da'wah on Facebook requires an integration of digital competence, deep religious knowledge, and commitment to Islamic ethical values. This study is expected to contribute theoretically to the development of Islamic communication studies and serve as a practical guide for preachers and Islamic institutions in designing ethical and effective digital da'wah strategies.